Groundwater quality monitoring study in the west region of Romania - Pacala Adina (Proceedings of the International Symposium on Analytical and Environmental Problems, 2023)
In the present study it was investigated the groundwater quality and its suitability for drinking purposes in several urban and rural areas from Timis, Arad and Bihor counties (West Region of Romania). We have established general and specific techniques for the analytical investigation of the inorganic and organic matrix in the environmental components of water from underground sources, for the identification and quantification of persistent pollutants with toxic potential, especially considering the presence of chlorobenzenes and organo-chlorinated pesticides, organophosphorus pesticides, plant treatment agents (triazine pesticides), benzene and benzene derivatives, polycyclic aromatic hydrocarbons and toxic metals, specifically tracking the presence of arsenic in groundwater resources in the Western Region of Romania.